High performance, self-powered ultraviolet photodetector based on a ZnO nanoarrays/GaN structure with a CdS insert layer. (23rd May 2017) - Zhou, Hai; Gui, Pengbin; Yang, Lu; Ye, Cong; Xue, Mengni; Mei, Jun; Song, Zehao; Wang, Hao
Abstract : A self-powered photodetector based on a ZnO nanoarrays/CdS/GaN structure with a responsivity as high as 176 mA W −1 at 300 nm. Abstract : Achieving high responsivity for a self-powered ultraviolet (UV) photodetector is challenging. Herein, we report a high responsivity self-powered UV photodetector based on a ZnO nanoarrays/GaN structure with a CdS insert layer whose responsivity reached as high as 176 mA W −1 at 300 nm, which is larger than the values of previously reported ZnO-based self-powered UV PDs. Moreover, based on the optimized CdS thickness with 5 cycle times, more than 1000 for the I ph / I dark ratio at the reverse biases was achieved. The device showed a good visible-blind UV photoresponse characteristic with the UV-visible responsivity ratio ( R 300nm / R 500nm ) reaching 48. Moreover, below the 350 nm UV region, the detectivity of the ZnO/CdS core–shell array PD was above 10 12 cm Hz 1/2 W −1, which is equivalent to that of the commercially available UV-enhanced Si photodiodes. The excellent photoelectric properties of the n-ZnO/CdS/p-GaN structure described above is due to the CdS insert layer, which was used as a carrier transition layer and realized a stepped energy level structure to effectively reduce the interfacial charge recombination and facilitate electron transfer.